Ocean's Eleven scene 12 – lost in transcription. (1st November 2020) - Messerli, Thomas C.
ABSTRACT: Research on film is typically transparent when it comes to identifying the excerpts of film on which it is based. Since analysts view film scenes in different reception situations and since even the same reception situation will lead to differing textual representations of data, the basis for researchers' analyses may nonetheless be underspecified. This article identifies aspects of data selection and transcription that are all too often neglected, but are critical for analysis and should not only be reflected on more thoroughly but also explicated to readers. It describes viewing constellations and analytical criteria and compares transcription conventions both theoretically and empirically, with the use of excerpts from Scene 12 of Ocean's Eleven (2001).